(untitled) (Linguostylistic Studies, 2015)
In the article the words and phrases, borrowed from other languages, are actively used in the modern Ukrainian language periodicals in a different spelling - Roman and Cyrillic, they were grouped by way of writing, analyzed the thematic unity of borrowing in the newspaper, determined their stylistic role. Characterized borrowing mainly of Anglo-American origin are caused by extralinguistic factors: the democratic processes in the society, cooperation with foreign countries, the lack of censorship and the like. There are several groups of foreign words and phrases: 1) those that are reproduced in Roman; 2) those that are written in Roman, and Cyrillic; 3) transcribed units. It was traced and described the use of neologisms in the language of periodicals, in particular, in the composition of names. Key words: barbarisms, stylistic role, language of Ukrainian periodicals, thematic focus, vocabulary diffusivity. References